Enteroendocrine cells and gut hormones as potential targets in the crossroad of the gut-kidney axis communication - Nery Neto, José Arimatéa de Oliveira; Yariwake, Victor Yuji; Câmara, Niels Olsen Saraiva; Andrade-Oliveira, Vinicius (Frontiers in Pharmacology, 2023)
Recent studies suggest that disruptions in intestinal homeostasis, such as changes in gut microbiota composition, infection, and inflammatory-related gut diseases, can be associated with kidney diseases. For instance, genomic investigations highlight how susceptibility genes linked to IgA nephropathy are also correlated with the risk of inflammatory bowel disease. Conversely, investigations demonstrate that the use of short-chain fatty acids, produced through fermentation by intestinal bacteria, protects kidney function in models of acute and chronic kidney diseases. Thus, the dialogue between the gut and kidney seems to be crucial in maintaining their proper function, although the factors governing this crosstalk are still emerging as the field evolves. In recent years, a series of studies have highlighted the significance of enteroendocrine cells (EECs), which are part of the secretory lineage of the gut epithelial cells, as important components in gut-kidney crosstalk. EECs are distributed throughout the epithelial layer and release more than 20 hormones in response to microenvironment stimuli. Interestingly, some of these hormones and/or their pathways such as Glucagon-Like Peptide 1 (GLP-1), GLP-2, gastrin, and somatostatin have been shown to exert renoprotective effects. Therefore, the present review explores the role of EECs and their hormones as regulators of gut-kidney crosstalk and their potential impact on kidney diseases. This comprehensive exploration underscores the substantial contribution of EEC hormones in mediating gut-kidney communication and their promising potential for the treatment of kidney diseases.